Non-baseline identification of delamination in plates using wavelet-aided fractal analysis of two-dimensional mode shapes. (November 2015) - Bai, RB; Radzieński, M; Cao, MS; Ostachowicz, W; Su, Z
Delamination is a typical form of damage in composite plates. Identification of delamination in plates has been a focus of increasing research interest in relatively recent years. This study develops a new approach, termed a scale waveform dimension analysis of two-dimensional mode shapes, to identify delamination in composite plates. The scale waveform dimension analysis comprises two components: decomposition of a mode shape into scale mode shapes and waveform dimension analysis of scale mode shapes. The first component acts as a splitter that broadly splits a noisy mode shape into three sets of trend-, noise-, and damage-scale mode shapes, from which the damage scale mode shapes can be selected for use in damage characterization; the second component functions as a detector to detect abnormalities of damage scale mode shapes, to indicate the presence and location of delamination. The efficacy of the method is numerically studied and experimentally examined using composite plates containing small delamination. The results show that the proposed method can identify delamination with great accuracy in noisy conditions, needing no intact baseline mode shapes nor any prior knowledge of either the material properties or boundary conditions of the plate being inspected.